Phosphorylation of dynamin-related protein 1 at Ser616 regulates mitochondrial fission and is involved in mitochondrial calcium uniporter-mediated neutrophil polarization and chemotaxis. (July 2017) - Zheng, Xianchong; Chen, Mimi; Meng, Xiaojing; Chu, Xinwei; Cai, Chunqing; Zou, Fei
Highlights: MCU promotes neutrophil polarization and chemotaxis. MCU regulates F-actin accumulation at the uropod of neutrophils during polarization. MCU mediates mitochondrial Ca 2+ uptake in neutrophils. MCU is responsible for Drp1 (S616)-dependent mitochondrial fission in neutrophils. Suppression of Drp1 inhibits neutrophil polarization and chemotaxis. Abstract: During an inflammatory response, polarization of neutrophils is necessary for effective chemotaxis and bacterial endocytosis. Ca 2+ uptake into mitochondria through the mitochondrial calcium uniporter (MCU) is crucial for cell metabolism, signaling and survival; however, the physiological role of MCU in human neutrophils remains unclear. Here we show that MCU is vital for the polarization and chemotaxis of neutrophils. Activation of MCU by spermine promotes neutrophil polarization and chemotaxis, whereas inhibition of MCU by Ru360 blunts both processes. We also provide evidence that this role of the MCU in neutrophils may result from modulation of mitochondrial fission by increased levels of pDrp1 S616 via accumulation of Ca 2+ into the mitochondrial matrix. Thus, our study identifies the dependence of neutrophil polarization and chemotaxis on the MCU and highlights the importance of regulating mitochondrial fission during the anti-inflammatory cascade in human neutrophils.